African cultural knowledge : themes and embedded beliefs - Kirwen, Michael C.; Maryknoll Institute of African Studies (Nairobi, Kenya) (Nairobi, Kenya : MIAS Books, 2005)
"Based on field research data collected and analyzed over the past seventeen years, the Maryknoll Institute of African Studies has categorized cultural knowledge into fifteen themes and thirty-five domains. The themes are the major values, symbols and ideas that bring wholeness and coherence to a culture. The themes explain the nature of life, the nature of creation, the nature of evil, etc. Underneath and within these themes are thirty-five cultural domains, that is, specific activities, rituals, attitudes and happenings that make up the ordinary events in the lives of human beings, from birth to death and beyond ... The book is divided into fifteen chapters, one for each foundational theme"--Intro., p. [1].
Creator God -- Ancestors -- Living dead -- Nominal reincarnation -- African lineage -- Leadership -- Adulthood and elderhood -- Bridewealth -- Marriage -- Polygyny -- Herbalist -- Diviner -- Witch -- Witchcraft -- Death -- Appendix A. Beliefs summarized in each chapter -- Appendix B. Respondents by nationality and ethnic groups.
Includes bibliographical references (p. 273-274).
Keywords: Africa -- Social life and customs; Africa -- Religion